Wasiyyah adoption and its barriers among Malaysian muslims - Hamid Ghul, Zahirah (2015)
Islamic inheritance system is usually explained within the conceptual framework of i.e. Faraidh, Wasiyyah (Will) and Hibah (gift). In Islam, there is no restriction on the transfers of wealth during the lifetime, however the distribution of estates upon death is strictly subjected to Faraidh and Wasiyyah rules. The salient feature of Faraidh on inheritance is subjected to a predetermined quantum of shares of the eligible heirs. Wasiyyah, on the other hand, is limited up to one-third of the estates’ value and is only allowed to be given to non-heirs. Wasiyyah can only be given to heirs with the consent of all eligible heirs. Islamic estate planning and Islamic inheritance system renders a new dimension in the Islamic economy and finance. Making a Wasiyyah (Will) is the more crucial element of the system. As such, this study selects Wasiyyah, which carries the meaning of a Will, as the main focus of this study. This study aims to investigate the factors that influence Wasiyyah Adoption and its barriers among Malaysian Muslims. The research model posits relationship between four factors: a) knowledge b) life events c) wealth management d) institutions (Wasiyyah writing providers).All this four factors are analysed using inferential analysis. Meanwhile, the barriers in Islamic inheritance distribution are analysed based on descriptive analysis. The theoretical model of this study is based on the Life Cycle, Altruism and Dynasty Model. In addition, Islamic theory of wealth is added as one of the theoretical underpinnings of this research. This research uses the self-administered survey method using electronic mail (email) questionnaires and self-administered questionnaire as its data collection method. About 300 questionnaires were distributed in Selangor and Klang Valley and only 170 questionnaires were returned. Another 61 were gathered from the online survey. Total of data gathered were 231 respondents. The data was analysed via Reliability, Validity, Descriptive and Binary Logistic Regression using SPSS version 20.0. The findings from this study show that knowledge and wealth management have a significant effect towards Wasiyyah practices while life events and institutions have no significant effect towards Wasiyyah practices. This indicates that the more knowledge one has about Islamic inheritance, the higher the intention to make a Wasiyyah is. Hence the higher the planning of wealth is, the higher the intention to make a Wasiyyah is. In terms of barriers in Islamic inheritance distribution, the biggest obstacle among all the factors are 1) estate management and 2)lengthy distribution process. This study offers several implications for both the academic and industry. It has covered the identified gaps and added value to the field of Wasiyyah practices and inheritance distribution.